Evaluating The E-marketing Requirements Necessary to Activate Distance Education in Syrian Universities (Journal of Hama University, 2021)
The recent technological developments and the great increase in the demand for learning without being bound by time and space, in addition to the trend of higher education in general towards internationalization and globalization, all these factors contributed to the emergence of a new model of higher education called virtual or digital education or distance education. Accordingly, this study aimed to assess the requirements of e-marketing necessary to activate distance education in Syrian universities, especially after the crisis of the Corona Virus outbreak, which emphasized the need to go to such kind of education because of the comprehensive closure imposed. Using the descriptive approach and through the data collected from the Webometrics and Alexa websites, this study concluded that the e-marketing requirements needed to activate distance education are not available in the current websites of Syrian universities and they are currently unable to bear the burdens of moving from physical education to e-learning Imposed by the Corona pandemic.